REVIEW OF THE FLEXURAL STRENGTH OF WASTE SHAVINGS AND ACACIA WOOD POWDER AS PARTICLE BOARD - Arianto; Lola Cassiophea; Petrisly Perkasa (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
In several developed countries, laminated wood products continue to be developed, these products can be laminated wood beams (glulam beams), laminated curved wood (bend wood), Stress Laminated Timber (SLT), Laminated Veneer Lumber (LVL) and other gluing products. Acacia is included in durable class 3 wood, quite resistant to weather and normal conditions but will easily be attacked by fungi and insects if placed in outdoor conditions that are too wet, not good for use directly on the ground. The research method used is a quantitative descriptive method. This research was carried out at the Forest Products Technology Laboratory and Forest Management Laboratory, Department of Forestry, Faculty of Agriculture, Palangka University. After testing the Acacia wood, the results of the test were obtained, then analysis was carried out on the data from the test results so that the following conclusions were obtained: The MOR value of Acacia wood in the KM1, KM2 and KM3 specimens was 66.08 N/mm², 196 .66 N/mm², and 188.83 N/mm². The MOE values for Acacia wood in specimens KM1, KM2 and KM3 are 919.91 N/mm², 932.47 N/mm² and 947.61 N/mm², respectively. The strength class of wood obtained from laboratory testing results is as follows: The strength class of particle board from acacia wood powder based on the specific gravity of the wood is included in wood strength class III with an average specific gravity value of 0.56, the strength class of particle board from Acacia wood powder based on the value MoR obtained from laboratory testing with an average MoR value of 183.96N/〖mm〗^2, strength class of particle board from Acacia wood powder based on MoE value obtained from laboratory testing with an average MoE value of 942.33 N/〖 mm〗^2